Land-Based Marine Pollution in Arctic - Haile, Fitsum Gebreselassie (UiT Norges arktiske universitet, 2014)
Land-based pollution represents the single most important cause of marine pollution. The threat of land-based pollution to the marine environment is a serious one since it mainly affects coastal waters, which are sites of high biological productivity. The occurrence of high concentrations of pollutants in the Arctic environment has been a concern for many years. Regional and international actions over the past two decades attempting to manage pollutants in the Arctic environment from land- based sources have produced recommendations that focus primarily on increasing cooperation in research and monitoring activities, not only among the Arctic governments themselves, but also including the interests and resources of non-polar countries. This paper demonstrates the complexity and breadth of the issues of land-based marine pollutions in Arctic, reviews the progress towards the management of risks and impacts associated with these pollutions, and comments on the proposed path towards rectification and appropriate management of these concerns.